Implementasi Sistem Manajemen Kinerja Berbasis Digital: Studi Kasus pada Perusahaan Multinasional di Indonesia - Nasar, Asbi; Susana Eky, Feny; Riwu, Lorens; Nasaruddin, Nasaruddin (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2026)
Digital transformation has fundamentally altered the landscape of performance management in multinational companies. This research aims to analyze the implementation of digital-based performance management systems in multinational companies in Indonesia, focusing on the implementation process, critical success factors, and their impact on evaluation effectiveness and employee productivity. Using a qualitative approach with library research methods, this study analyzes various primary and secondary literature sources from 2019-2024. The results indicate that implementing digital performance management systems requires a gradual and structured approach, considering technological aspects, human resources, and organizational culture. Critical success factors include technological infrastructure maturity, employee digital competency, effective change management, and consistent leadership support. Digital system implementation results in significant improvements in performance evaluation accuracy, process efficiency, transparency, and employee productivity. This research provides theoretical and practical contributions to the development of digital HR management in the digital transformation era.